A comparison of CF4, CBrF3 and C2Br2F4 plasmas: Physical parameters and densities of atomic species. (June 2022) - Miakonkikh, Andrey; Kuzmenko, Vitaly; Efremov, Alexander; Rudenko, Konstantin
Abstract: In this work, we performed the comparative study of CF4, CBrF3 and C2 Br2 F4 inductively coupled low temperature plasmas under typical reactive-ion etching conditions. The research scheme included plasma diagnostics by Langmuir probes, optical emission spectroscopy and 0-dimensional (global) modeling for CF4 plasma. The latter was to verify the experimental data for their relevancy. The main focus was on electrons- and ions-related plasma characteristics as well as on densities of F and Br atoms which do work as chemical etchants for Si-based materials. It was found that all three plasma systems exhibit similar changes of above parameters vs. gas pressure. Principal features of CBrF3 and C2 Br2 F4 plasmas in respect to CF4 are a) lower electron temperatures; b) higher plasma densities and electronegativities; and c) reduced densities of F atoms with the condition of [F] > [Br]. The last phenomenon is probably due to Br2  + F → BrF + Br reaction mechanism supported by the fast 2Br → Br2 recombination on chamber walls. Hence, the combination of higher ion density and lower F atoms density in bromine-containing gases provides their advantage in neutral/charged ratios and thus, in the etching anisotropy. Highlights: ICP plasma of bromofluorocarbons CBrF3 and C2 Br2 F4 were compared with CF4 plasma. Bromofluorocarbons ICP plasma have lower electron temperatures than CF4 plasma. Plasma densities in CBrF3 and C2 Br2 F4 plasma are several times higher than in CF4 . CBrF3 and C2 Br2 F4 plasma have 5 times lower neutral/charged ratios than CF4 plasma. Fluorine concentration in CBrF3 and C2 Br2 F4 plasmas is higher than Br concentration.